2005
DOI: 10.1074/jbc.m500924200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, Insulin, and Dietary Signals Cooperatively Regulate Longevity Signals to Enhance Resistance to Oxidative Stress in Mice

Abstract: To investigate the biological significance of a longevity mutation found in daf-2 of Caenorhabditis elegans, we generated a homologous murine model by replacing Pro-1195 of insulin receptors with Leu using a targeted knock-in strategy. Homozygous mice died in the neonatal stage from diabetic ketoacidosis, whereas heterozygous mice showed the suppressed kinase activity of the insulin receptor but grew normally without spontaneously developing diabetes during adulthood. We examined heterozygous insulin receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 48 publications
2
54
0
2
Order By: Relevance
“…When this transcription factor is activated, it is imported to the nucleus, where it stimulates transcription of MnSOD and GPx genes (Borras et al, 2005). Although, some reports show that female rats have higher antioxidant concentration and activity than male rats (Borras et al, 2003;Baba et al, 2005), others did not found such difference (Jang et al, 2004;Sverko et al, 2002Sverko et al, , 2004. This indicates that estrogen regulation may increase antioxidant defenses in some, but not in all strains.…”
Section: Discussionmentioning
confidence: 68%
“…When this transcription factor is activated, it is imported to the nucleus, where it stimulates transcription of MnSOD and GPx genes (Borras et al, 2005). Although, some reports show that female rats have higher antioxidant concentration and activity than male rats (Borras et al, 2003;Baba et al, 2005), others did not found such difference (Jang et al, 2004;Sverko et al, 2002Sverko et al, , 2004. This indicates that estrogen regulation may increase antioxidant defenses in some, but not in all strains.…”
Section: Discussionmentioning
confidence: 68%
“…In a manner similar to the connections between the ISC and aging in other organisms, there is evidence for a role for IGF-I in the control of longevity in mammals. Specifically, mice heterozygous for an IGF receptor mutation exhibited a 33% increase in longevity and upregulated MnSOD activity [21]. In mice, as in fruit flies, overexpression of catalase targeted to the mitochondria lengthened lifespan and reduced oxidative tissue damage, including H 2 O 2 -induced aconitase inactivation and the development of mitochondrial deletions relative to control animals [22].…”
Section: The Isc Innate Immunity and Aging In Mammalsmentioning
confidence: 99%
“…This pathway is also implicated in environmental stress response pathways and longevity in C. elegans as well as other organisms (Kenyon et al 1993;Tatar et al 2003;Baba et al 2005;Gami and Wolkow 2006). These studies have identified conserved host factors used against virulent pathogens with a generalized host range.…”
mentioning
confidence: 99%